The Potential of Noni (Morinda citrifolia L.) as an Anti-Diabetic - Fadlilah, Synta Haqqul; De Silva, Ghea; Suhartomo, Dalri Muhammad; Yusan, Rizak Tiara (Universitas Muhammadiyah Semarang, 2024)
Background: Diabetes Mellitus (DM) is still a major health problem in the world today because the prevalence remains increasing. Type 2 diabetes is the most common type of diabetes, accounting for over 90% of all diabetes cases. This disease is characterized by insulin resistance, where the body cannot fully respond to insulin. As a result, glucose levels in the blood continue to increase (hyperglycemia). The main of Type 2 DM management is a healthy lifestyle. In addition, pharmacological therapy is also needed to keep blood glucose levels in diabetics under control. However, antidiabetic medicines can cause some side effects. Therefore, the development of alternative diabetes therapy has been done to minimize side effects. One of the herbal ingredients that are being studied for its potential as an anti-diabetic is noni (Morinda citrifolia L.).Objective: The aim of the study is to review and find out more about the potential of noni (Morinda citrifolia L.) as an anti-diabetic.Methods: This research is included in the type of literature review. The kinds of literature are English and Indonesian language research articles related to the topic searched by using database sources from ProQuest, PubMed, ScienceDirect, and Google Scholar. The research articles were published in the last 10 years (2012 to 2022). Results: There are 14 kinds of literature that match the topic of study. A total of 12 kinds of literature are in vivo studies on animals and 2 literature studies on humans. The result shows that noni has an antidiabetic effect by lowering blood glucose levels and improving other parameters. Parts of Noni that have the potential to control Type 2 DM are fruit and leaves, which can be in the form of extracts, juices, or fermented products. Further research is needed to evaluate the toxicity, the content of active compounds, and the expression of genes related to Type 2 DM for ensuring the mechanism of noni in controlling hyperglycemia. Human studies with more respondents are also needed to confirm the findings of existing studies. Conclusion: Noni has an antidiabetic effect by lowering blood glucose levels and improving other parameters. Based on human studies, noni fruit juice can serve as a suitable addition to the diet of Type 2 DM patients.